An Improved Matlab-Simulink Model of PV Module considering Ambient Conditions - Ayaz, R.; Nakir, I.; Tanrioven, M. (HINDAWI LTD, 2014)
A photovoltaic (PV) model is proposed on Matlab/Simulink environment considering the real atmospheric conditions and this PV model is tested with different PV panels technologies (monocrystalline silicon, polycrystalline silicon, and thin film). The meteorological data of Istanbul-the location of the study-such as irradiance, cell temperature, and wind speed are taken into account in the proposed model for each technology. Eventually, the power outputs of the PV module under real atmospheric conditions are measured for resistive loading and these powers are compared with the results of proposed PV model. As a result of the comparison, it is shown that the proposed model is more compatible for monocrystal silicon and thin-film modules; however, it does not show a good correlation with polycrystalline silicon PV module.
Keywords: Chemistry; Energy & Fuels; Optics; Physics